2018
DOI: 10.4049/jimmunol.1600608
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Vaccines: Conduits for Protective Antigens

Abstract: Vaccines afford a better and more cost-effective approach to combatting infectious diseases than continued reliance on antibiotics or antiviral or antiparasite drugs in the current era of increasing incidences of diseases caused by drug-resistant pathogens. Recombinant attenuated vaccines (RASVs) have been significantly improved to exhibit the same or better attributes than wild-type parental strains to colonize internal lymphoid tissues and persist there to serve as factories to continuously synthesize and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 150 publications
0
60
0
Order By: Relevance
“…However, the dependence on injection immunization severely limits the application of DNA vaccine in field production. Therefore, some researchers have turned their eyes on the use of bacterial vectors to deliver plasmid DNA by oral immunization, such as lactic acid bacteria (LeCureux and Dean ), Salmonella (Clark‐Curtiss and Curtiss ) and Listeria monocytogenes (Deng et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the dependence on injection immunization severely limits the application of DNA vaccine in field production. Therefore, some researchers have turned their eyes on the use of bacterial vectors to deliver plasmid DNA by oral immunization, such as lactic acid bacteria (LeCureux and Dean ), Salmonella (Clark‐Curtiss and Curtiss ) and Listeria monocytogenes (Deng et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the dependence on injection immunization severely limits the application of DNA vaccine in field production. Therefore, some researchers have turned their eyes on the use of bacterial vectors to deliver plasmid DNA by oral immunization, such as lactic acid bacteria (LeCureux and Dean 2018), Salmonella (Clark- Curtiss and Curtiss 2018) and Listeria monocytogenes (Deng et al 2018). Of note, a novel technology to design more efficient vaccines using a kind of special recombinant attenuated Salmonella vaccines (RASVs) (Curtiss et al 2010) with a unique regulated delayed lysis system allows the vaccine strains to colonize host lymphoid tissues and result in cell death by lysis after several rounds of replication, thereby preventing spread of the vaccine strains into the environment and possibly leading to unintended immunizations (Kong et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical for live vaccine development to achieve a proper balance between attenuation and immunogenicity through the use of new vaccine development technologies such as regulated delayed in vivo attenuation and regulated delayed in vivo antigen synthesis, which enables vaccines to e ciently colonize host tissues, thereby inducing a su cient immune response against protective antigens synthesized in the vaccine vectors [29,37]. The key strategy for achieving regulated delayed in vivo attenuation relies on regulating essential gene expression by replacing the promoter of a gene of interest with the regulated promoter, such as arabinose-regulated araC P BAD [30,37]. Our previous results already demonstrated that this strategy is bene cial for inducing higher immune responses against vector delivered antigens [23,35].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no LacI is expressed without arabinose in the growth environment of strain χ9241(pYA4088), resulting in production of the heterologous PspA that are carried on pYA4088. This regulated delayed expressed system has been widely used to evaluate the effects of other mutations on immunogenicity against heterologous antigens [28][29][30]. In this work, we constructed an ECA-de cient Salmonella Typhimurium mutant by deleting the entire ECA operon from wecA to wecG based on the wild type strain χ3761 [31]and the attenuated live vaccine strain χ9241 [32], and evaluated the effect of removing the whole ECA operon on the virulence and immunogenicity of wild type Salmonella Typhimurium and its attenuated mutants.…”
Section: Introductionmentioning
confidence: 99%
“…Other Salmonella products such as LPS would be expected to further enhance immune responses by triggering TLR4 [18, 19]. Indeed, live attenuated Salmonella have multiple potential advantages as vaccine vectors and have been used to express foreign antigens against infectious diseases and cancers [2022]. They directly target the intestinal M cells overlying the gut-associated lymphoid tissues (GALT) [21, 2326], have large ‘carrying’ capacity [27] and are easy to manipulate both in the laboratory and at industrial scale.…”
Section: Introductionmentioning
confidence: 99%